ORIENTASI PEMBELAJARAN IPS PADA PENDIDIKAN SEKOLAH DASAR: MEMBANGUN KETERAMPILAN BERSOSIAL SISWA - M. Muhlis; Sholahuddin Al Ayyubi; Khairil Candra Wijaya; Istiningsih; Suci Skar Kinanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Globalization has entered every aspect of human life in modern times, including the lives of students in their homes, their schools, and their societies. Although globalization has many positive effects, it also has negative effects, including national social problems that are of great concern today. Therefore, strengthening social studies learning is needed so that social studies studies are not only focused on the cognitive domain. In addition, social studies studies can help students acquire better social skills, so that they can live more meaningfully and efficiently in the modern era. This research is a research that uses the literature review method. Globalization has entered every aspect of human life in modern times, including the lives of students in their homes, their schools, and their societies. Although globalization has many positive effects, it also has negative effects, including national social problems that are of great concern today. Therefore, strengthening social studies learning is needed so that social studies studies are not only focused on the cognitive domain. In addition, social studies studies can help students acquire better social skills, so that they can live more meaningfully and efficiently in the modern era. This research is a research that uses the literature review method. approach. In addition, social studies learning in elementary school is essential to prepare students to become active and responsible citizens who can interact and socialize with others